Physical activity as a stressbuster: Insights from university students - Mohammed, Redhwan Ali Esmail (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to investigate how university students’ psychological stress can be reduced by physical activity. Using a stratified random sampling technique, 580 students (52.93% males and 47.07% females) were chosen from three private institutions in Riyadh, Saudi Arabia. Participants were emailed a questionnaire with 20 questions that was created based on prior research. The findings indicated that exercise positively influenced mood, reduced anxiety and depression, improved focus, and enhanced overall quality of life. Physical activity was also found to lower psychological stress and support mental health. Differences in responses were observed across gender, academic level, and college, with male students reporting slightly higher mean scores than females. Statistical analysis revealed significant gender differences (α ≤ 0.05) in perceptions of the role of physical activity in reducing psychological stress, favoring male students. This study highlights the importance of physical activity in helping university students manage psychological stress and emphasizes the necessity of integrating and promoting physical activity programs within the campus setting.